1990
DOI: 10.1111/j.1469-7998.1990.tb04031.x
|View full text |Cite
|
Sign up to set email alerts
|

On the optimal growth of the alimentary tract in avian postembryonic development

Abstract: It was shown in the mathematical model described elsewhere that when growth rate of the chicks is maximized and not constrained by the food availability, the optimal relationship between body mass and alimentary tract mass should conform to a single straight line, or two‐, or three‐segmented straight lines. Here, we present the data on growth of 11 bird species, and we test the model using the mass of intestines as an indicator of growth of the alimentary tract. The results support the predictions of the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…However, most studies in birds have shown that ospring of birds that breed the earliest grow and survive best (Perrins 1970;Daan et al 1988;Sedinger and Flint 1991;Cooch et al 1991a; but see van Noordwijk et al 1995). A ®rst explanation of this paradox could be that growth in birds is relatively insensitive to natural variation in food supply (Konarzewski et al 1989(Konarzewski et al , 1990. However, there is experimental evidence that protein and energy intakes during the nestling period aect growth rate and ®nal adult size (Johnson 1971;Jùrgensen and Blix 1985;Boag 1987;Lindholm et al 1994).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, most studies in birds have shown that ospring of birds that breed the earliest grow and survive best (Perrins 1970;Daan et al 1988;Sedinger and Flint 1991;Cooch et al 1991a; but see van Noordwijk et al 1995). A ®rst explanation of this paradox could be that growth in birds is relatively insensitive to natural variation in food supply (Konarzewski et al 1989(Konarzewski et al , 1990. However, there is experimental evidence that protein and energy intakes during the nestling period aect growth rate and ®nal adult size (Johnson 1971;Jùrgensen and Blix 1985;Boag 1987;Lindholm et al 1994).…”
Section: Introductionmentioning
confidence: 92%
“…Thus, there is controversy about how much variability in growth rate can be explained by variation in food. Some authors have argued that growth rate is largely constrained by physiological factors rather than by food availability (Ricklefs 1983;Konarzewski et al 1989Konarzewski et al , 1990. However, most of these studies were on altricial birds which are fed by their parents with protein-rich food such as insects.…”
Section: Timing Of Hatch and Food Availabilitymentioning
confidence: 99%
“…An increased growth rate contributes again to decreased mortality of the young. When food available to the young is not a limiting factor, it is optimal to allocate as much energy as possible to the organs related to energy assimilation at the early stage of the growth (Konarzewski et al 1990). Thus, a maximum growth rate is possible when the young minimize investments into locomotor activity.…”
Section: Correlated Evolution Of Parental Care and Endothermymentioning
confidence: 99%
“…Intestinal development has been the subject of recent reviews (Moran, 1985;Dibner et al, 1996;Sell, 1996;Noy and Sklan, 1997;and Uni, 1999). Functional maturation of the small intestine is both a physical and physiological process and is one of the main constraints to early growth after hatching (Konarzewski et al, 1989(Konarzewski et al, , 1990Ricklefs et al, 1998). Physiological maturation (in terms of digestive and absorptive functionality) of the digestive tract involves the increased production of pancreatic and intestinal enzymes (Nitsan et al, 1991a,b;Sell et al, 1991;Pinchasov and Noy, 1994) and changes in nutrient transporters (Holdsworth and Hastings-Wilson;1967;Shehata et al, 1984;Obst and Diamond, 1992).…”
Section: Poults From Young Hens: Differences In Intestinal Developmentmentioning
confidence: 96%